Evaluation of teratogenic potency of colchicine by using Biomphalaria alexandrina snail embryo as an indicator - Omran, Nahla E.E; Eissa, Samia H.; Salem, Hoda K.; Kandeil, Manar A. (JOURNAL OF ADVANCES IN BIOLOGY, 2013)
The present study was planned to follow up the teratogenic potency of cholchicine on the developmental stages of Biomphalaria alexandrina. The results revealed that trochophore stage can be considered as a specific stage for colchicine at which the embryos are highly sensitive. The fractionation of proteins by SDS-PAGE electrophoresis showed that colchicine induced disappearance of the band with the molecular weight 158.5 kD and the increase in the intensity of some bands. The impact of colchicine against egg masses containing trochophore larvae induced many disturbances of organic substances such as a significant decrease in the total protein (58.96 % decreases), lipid (35.11 % decrease) and a glycogen levels (42.84 % decrease). The subsequent or co-treatment with recovery agents such as vitamin C, holothurin extract and folic acid were investigated. The teratogenic effect of colchicine on the morphogenesis of snail embryos is so intensive that the malformations couldn’t be reversed by subsequent or co-treatment with vitamin C and holothurin. But, it is worth reporting that concomitant addition of folic acid to malformed embryos succeeded to produce significant amelioration of the teratogenic deformities induced by colchicine reached to 86.7 %. But, folic acid has a very slight recovery effect on the embryos post-treated with it. In conclusion the B. alexandrina snail embryo can be used as a bioindicator for studying the teratogenic effect of colchicine. Also using folic acid serves a good prophylactic agent against teratogenicity induced by colchicine.